Ecumenical Performance Analytics: A KPI Framework for Christian Unity and Institutional Dialogue - MoghadasNian, SeyyedAbdolHojjat; Alizadeh Mousavi, Seyed Mahdi; Hosseinpoor, Seyed Mohammad Mahdi; Bagheri, Akbar (21th International Conference on Management Research and Humanities in Iran, 2025)
This study introduces the Ecumenical Christian KPI Framework (ECKF) as a strategic model for transforming theological aspirations of Christian unity into a measurable, performance-driven system. The research addresses the central challenge of operationalizing ecumenism by constructing a comprehensive framework comprising 12 strategic axes and 110 validated Key Performance Indicators (KPIs). Utilizing a mixed-methods approach, the study integrates expert Delphi analysis, document evaluation of institutional charters, and quantitative prioritization using Analytic Hierarchy Process (AHP) and Principal Component Analysis (PCA). Findings indicate a strong consensus around digital theology, institutional governance, and cross-denominational benchmarks as critical drivers of ecumenical success. The framework provides actionable metrics to guide policy, interchurch collaboration, and digital transformation initiatives across ecclesiastical structures. Theoretically, the ECKF contributes a novel KPI-based paradigm to the study of ecumenism, aligning theological ethics with performance science. Practically, it enables the development of real-time dashboards for measuring theological convergence, interfaith impact, and digital participation. The model is adaptable for application across diverse ecclesial traditions, supporting both strategic unity and institutional resilience. Recommendations are offered for policymakers, religious leaders, and digital theologians seeking to operationalize unity through performance governance. The study concludes by outlining future research directions involving AI integration, youth inclusion metrics, and digital ethics in virtual religious systems.